Citizenship, Education and Violence On Disrupted Potentialities and Becoming - Waghid, Yusef; Davids, Nuraan; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
The focus of this book is to offer a humane rocesponse to dealing with violence. An interpretive analysis is presented in order to think differently about violence in schools and about how a citizenship education of becoming can deal with the unpredictable consequences of violence in its own potentiality. It seems to the authors that, given the confident onslaught of violence, there is nothing left to do but to offer insight into the nature of violence itself and, by so doing, to search for unexplored ways of humane response and being. The authors are not pretending to hold a magic wand that will sanctify schools into the safe zones that they ought to be and as which they should serve in any society. This would be both presumptuous and misleading. What one is looking and hoping for, however, is a renewed engagement, a slight tilting of the perspective, so that something other than how we have always responded to violence perhaps will emerge. The authors are confident that such a deconstructive approach to violence in schools through the lens of a reconsidered view of citizenship education can assist them and others to wrestle with its potential for destruction that can be changed into options for co-belonging of a non-violent, if not peaceful, kind.
Keywords: Education; Education; Education (general).